The reinstatement of the expression phase of morphine-induced conditioned place preference in male Wistar rats under ventral tegmental area stimulation and brief inactivation - Mozhgan Ghobadi Pour; Hojjatollah Alaei (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Previous research has found that the electrical stimulation of the ventral tegmental area (VTA) is involved in drug-dependent behaviors and plays a role in reward-seeking. However, the mechanisms remain unknown, especially the effect of electrical stimulation on this area. Therefore, this study aimed to investigate how the electrical stimulation and the temporary inactivation of VTA affect the morphine- dependent behavior in male rats. Experimental approach: The adult Wistar male rats were anesthetized with ketamine and xylazine. The stimulation electrode (unilaterally) and the microinjection cannula (bilaterally) were implanted into the VTA, stereotaxically. Then, the rats underwent three-day of repeated conditioning with subcutaneous morphine (0.5 or 5 mg/kg) injections, in the conditioned place preference apparatus, followed by four-day forced abstinence, which altered their conditioning response to a morphine (0.5 mg/kg) priming dose on the ninth day. On that day, rats were given high- or low-intensity electrical stimulation or reversible inactivation with lidocaine (0.5 pL/site) in the VTA. Findings/Results: Results showed that the electrical stimulation of the VTA with the high intensity (150 μA/rat), had a minimal effect on the expression of morphine-induced place conditioning in rats treated with a high dose (5 mg/kg) of morphine. However, the reversible inactivation of the VTA with lidocaine greatly increased place preference in rats treated with a low dose (0.5 mg/kg) of morphine. Additionally, the reinstatement of 0.5 mg/kg morphine-treated rats was observed after lidocaine infusion into the VTA. Conclusion and implications: These results suggest that VTA electrical stimulation suppresses neuronal activation, but the priming dose causes reinstatement. The VTA may be a potential target for deep brain stimulation-based treatment of intractable disorders induced by substance abuse.